Conclusions of potato resistant perspective sources search to potato brown rot - Krym , I. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2023)
Goal. The laboratory technique for potato varieties resistance determining to potato brown rot causative agent during artificial infecting improves and potential resistance sources search for the following breeding work usage. Methods. The laboratory methods conducted by artificial affecting of plant material by suspension of potato brown rot — tubers parts in tubes and plants’ aboveground part, which grew in artificial substrate during studies. It allowed to follow the standard terms in repetition researches. Results. The resistance (susceptibility) to potato brown rot determined on 63 potato samples of different origin in controlled laboratory terms. The healthy well-developed plants after opening 5—6 plants selected for experiments. They grew on artificial substrate. It allowed to provide comfortability and velocity of work, follow the standard terms during the put of some repeatability of experiment, conduct terms of phytosanitary security, decrease number of waste, for the retreating. The fast disease development observed after aboveground plant affecting by bacterium suspension. There were the following symptoms: ill leaves faded, changing colour on brown or bronze. They curled and then died, the stem became brown color around the vascular bundle. It spread from inoculation place. Then the plants faded through the destroy of water transport by pathogen defeating vessels. It was the most spread on varieties Agatha, Vedruska, Volodarka, Gorlytsya, Malynska bila,Solntsedar or Phantasy. The lowest defeating received varieties Glazurna, Knyazha, Kobza, Lugivska, Poliske dzerelo, Prolisok, Slauta, Strumok and Favor. Conclusions. There were any varieties with enough resistance (susceptibility) to brown rot determined among the researched samples in laboratory terms. So there are no varieties with enough resistance for the following breeding work. This technique of researched plants growing may be used for laboratory testing conducting on varieties resistance and to other phytopathogens.